Concept of Islamic Education Management At Azzakiyyah Islamic Boarding School in Yogyakarta - Rakhmad Agung Hidayatullah; Aisyah Khoniwardah; Aisyah Nur Rahmah; Rindi Rahmawati FTN; Amir Reza Kusuma (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Educational institutions are developing more and more complex along with the development of technology and changing times. A well-organized and correctly organized organization is needed in keeping up with the challenges of the times and future changes. A management approach will be needed in the management of complex education implementation. The need for a new discovery and an increase in human resources so that the organization can develop and survive in the modern era. Education is an important thing for humans to face their survival until the future. Education is required to be able to deliver humans to real life. Education as it is known today not only covers in general but also specific to Islamic education. Where Islamic education is required to be able to produce reliable next generations both in general education and religion. Islamic education is essentially an educational activity that is organized or established with the desire and intention to embody Islamic teachings and values. Islamic education in Indonesia can be manifested in several forms such as Islamic boarding schools, madrasas, Islamic